The leader's guide to lateral thinking skills unlocking the creativity and innovation in you and your team - Paul Sloane (London KoganPage, 2017)
Acknowledgements -- Introduction -- The need for innovation -- Characteristics of the lateral leader -- The innovation test -- Laying the foundations for change -- Making the vision real -- Challenge your assumptions -- Ask searching questions -- Take a different view -- Combine the unusual -- Adapt, adopt, improve -- Break the rules -- Analyse first -- Increase the yield -- Introduce the random -- Evaluate -- Implement -- Welcome failure -- Use the team -- Organizing for innovation -- Common mistakes -- 21 great ways to innovate -- The lateral leadership course -- Appendix 1: Tools and techniques -- Appendix 2: Answers to lateral thinking puzzles -- References and recommended reading -- Index.
ncludes bibliographical references and index.
Keywords: Creative ability in business